#### Answer

The solution is -$\frac{7}{10}$

#### Work Step by Step

$\frac{2}{5}$ + y= -$\frac{3}{10}$
$\frac{2}{5}$+y -$\frac{2}{5}$=- $\frac{3}{10}$-$\frac{2}{5}$
Subtract $\frac{2}{5}$ to both sides
$y=-\frac{3}{10}$-$\frac{4}{10}$
LCD of the denominators 10 and 5 is 10
$y=-\frac{3}{10}$-$\frac{2}{5}$
$y=-\frac{3}{10}$-$\frac{4}{10}$
$y=\frac{-3-4}{10}$
$y= -\frac{7}{10}$
The solution is -$\frac{7}{10}$
Check
Replace y with $\frac{-7}{10}$
$\frac{2}{5}$ +y=-$\frac{3}{10}$
$\frac{2}{5}$ -$\frac{7}{10}$=-$\frac{3}{10}$
$\frac{4}{10}$ -$\frac{7}{10}$=-$\frac{3}{10}$
-$\frac{3}{10}$=-$\frac{3}{10}$